SAT0150 Comparative Risk of Malignancy with Initiaton of Abatacept and Other Biologics in Patients with Rheumatoid Arthritis: A Cohort Analysis of A United States Claims Database. (15th July 2016) - Suissa, S.; Baker, N.; Kawabata, H.; Ray, N.; Simon, T.
Abstract : Background: Patients with RA may be at an increased risk for malignancies compared with the general population, and treatment with TNF inhibitors have been reported to further increase this risk. 1 Abatacept, the first selective co-stimulation modulator for the treatment of RA, has a mechanism of action that is fundamentally different from that of other biologic agents. Objectives: This cohort study aimed to compare the risk of malignancy between patients initiating abatacept and patients initiating other biologic treatments. Methods: Adult patients diagnosed with RA in the MarketScan® Commercial and Supplemental Medicare database who initiated treatment with abatacept or another biologic treatment between 1 July 2006 and 30 September 2014 were eligible for inclusion in the analysis. Patients were required to have at least 180 days of continuous health plan enrolment prior to, and ≥1 day following, initiation of the qualifying RA treatment. Patients were presumed to have initiated a treatment if there was no claim for that particular drug in the 180 days prior to the index date. Therefore, patients initiating abatacept or another biologic treatment may be initiating a biologic for the first time or switching from one biologic to another. Malignancies were identified by International Classification of Diseases, Ninth Revision (ICD-9) diagnosis codes. Patients were followed from 180 days after the date of initiation of abatacept or another biologic treatment until occurrence of a malignancy (identified by ICD-9 code), end of enrolment in the database or end of data collection, whichever occurred first. Patients who had an ICD-9 code for a malignancy in the 6 months prior to or after the date of initiation were excluded. Crude incidence rates were calculated for each cohort. After matching each initiator of abatacept with 1 or 2 initiators of other biologic treatments on the propensity score, a Cox regression analysis was performed to estimate the hazard ratio. Results: A total of 17, 670 patients initiating abatacept and 50, 641 initiating another biologic were identified. During an average follow-up of 1.4 years for abatacept initiators and 1.6 years for other biologic initiators, there were 1132 and 2933 patients with an incident event of malignancy, respectively. This resulted in incidence rates of 44 (95% CI: 42, 47) and 36 (35, 38) per 1000 person-years in abatacept initiators and other biologic initiators, respectively. The propensity score analysis resulted in 17, 517 patients initiating abatacept matched with 32, 277 patients initiating another biologic. After adjusting for prior biologic treatment, the hazard ratio of malignancy with abatacept relative to other biologic agents was 1.10 (0.98, 1.23). Hazard ratios for lung cancer, lymphoma, breast cancer and non-melanoma skin cancer were also similar between the two. Conclusions: In this large, real-world study of patients treated for RA, the risk of malignancy was not significantly different for those who initiated abatacept compared with those who initiated other biologic agents. References: Mercer LK, et al. Ann Rheum Dis 2015;74:1087–93. Disclosure of Interest: S. Suissa Consultant for: Bristol-Myers Squibb, Genentech, Roche, N. Baker Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, H. Kawabata Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, N. Ray: None declared, T. Simon Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb